Pengaruh Media Sosial Instagram dan E-Wom (Electronic Word of Mouth) Terhadap Keputusan Pembelian Konsumen - Muhamad Sahal Mahpud; Leny Muniroh; Hendri Maulana (Institute of Advanced Knowledge and Science, 2024)
This study aims to determine the effect of Instagram Social Media and E-WOM (Electronic Word Of Mouth) on Purchasing Decisions of Ruby UMKM consumers. The research method used is an expalani survey method with a quantitative approach. The population in this study were 100 respondents who followed the Instagram account